2001
DOI: 10.1111/0272-4332.212113
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic Determinants of Health‐ and Food Safety‐Related Risk Perceptions

Abstract: Individual and societal perceptions of food-related health risks are multidimensional and complex. Social, political, psychological, and economic factors interact with technological factors and affect perceptions in complex ways. Previous research found that the significant determinants of risk perceptions include socioeconomic and behavioral variables. Most of these past results are based on two-way comparisons and factor analysis. The objective of this study was to analyze the significance of socioeconomic d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

34
228
5
5

Year Published

2006
2006
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 317 publications
(272 citation statements)
references
References 8 publications
34
228
5
5
Order By: Relevance
“…Some evidence suggests that households with children report greater concerns about food risks (Dosman et al 2001), but others do not find a significant effect (Miles et al 2004). Several studies find that education increases confidence about food safety, although the causal mechanism is unclear (Baiardi, Puglisi, and Scabrosetti 2016;De Jonge et al 2007).…”
Section: Public Perceptions Of Biological and Chemical/technical Foodmentioning
confidence: 99%
“…Some evidence suggests that households with children report greater concerns about food risks (Dosman et al 2001), but others do not find a significant effect (Miles et al 2004). Several studies find that education increases confidence about food safety, although the causal mechanism is unclear (Baiardi, Puglisi, and Scabrosetti 2016;De Jonge et al 2007).…”
Section: Public Perceptions Of Biological and Chemical/technical Foodmentioning
confidence: 99%
“…suggests that there is a negative relationship between educational level and risk perception, implying that the less educated have higher risk perceptions (Dosman et al, 2001;Savage 1993). Moreover, Chiricos et al (2000) found that those with lower levels of education have higher levels of perceived risk of criminal victimization.…”
Section: Educational Levelmentioning
confidence: 99%
“…1;(1996, Slovic (1999), Rowe and Wright (2001) and Kellens, Zaalberg, Neutens, Vanneuville, and De Maeyer (2011), tend to judge risks as both smaller and less problematic than do females, Siegrist (2000) found that gender was a weak predictor of risks perceived. Savage (1993) and Dosman, Wiktor, and Steve (2001) explain further that females perceive only particular risks to be larger; these include house fires, road accidents, food risks, violence, radioactive waste and global warming. Educational level was found not to be an important influencer of risk perception in Jordan.…”
Section: Risk Perception and Demographical Variablesmentioning
confidence: 99%